How do New Ventures Thrive in Ecosystem Venturing: The Impacts of Alliance Strategy and Technology Interdependence - Chen, Xiafei; Yang, Yi; Wei, Jiang (Journal of Management Studies, 2025)
AbstractNew ventures in an innovation ecosystem can not only receive benefits, but also face challenges. It is important to examine defence mechanisms that new ventures can employ for their healthy development in the innovation ecosystem. Based on resource dependence theory, combining with arguments from innovation ecosystems literature, this paper proposes that new ventures’ technological alliances with core competitors of ecosystem investors can be used as a social defence in ecosystem venturing. Furthermore, we investigate the moderator effects of technological interdependence – technological similarity and technological complementarity on the impacts of such a defence mechanism. Using longitudinal information of 4903 investor‐investee dyads in ecosystem venturing, we find that (1) technological alliances with core competitors of the ecosystem investor has a positive relationship to venture performance, and (2) such relationship is negatively moderated by technological complementarity. Our findings provide important implications for research on innovation ecosystems and resource dependence theory.